2014
DOI: 10.1089/tmj.2013.0226
|View full text |Cite
|
Sign up to set email alerts
|

mCare: Using Secure Mobile Technology to Support Soldier Reintegration and Rehabilitation

Abstract: The mCare pilot project demonstrated the feasibility and administrative effectiveness of a scalable mhealth application using secure mobile messaging and information exchanges, including personalized patient education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…16 Likewise, a pilot study of mCare found an increase in adherence to health care appointments. 17 Many health care providers recognize that, despite how necessary self-care is, it is not necessarily the highest priority of their patients, and/or patients have competing priorities. The mCare team hypothesized that a more satisfying user experience would lead to consistent and sustained usage.…”
Section: Discussionmentioning
confidence: 99%
“…16 Likewise, a pilot study of mCare found an increase in adherence to health care appointments. 17 Many health care providers recognize that, despite how necessary self-care is, it is not necessarily the highest priority of their patients, and/or patients have competing priorities. The mCare team hypothesized that a more satisfying user experience would lead to consistent and sustained usage.…”
Section: Discussionmentioning
confidence: 99%
“…For people with severe mental illness and life altering diseases, such healthcare services can provide continuous support, empathy and guidance for the caregiver and the patient. mCare was also used for soldiers who have returned from their service with the aim to animate them, provoke empathy, improve contact rates and positively impact the military healthcare system using mobile messaging [30], [31].…”
Section: 6mentioning
confidence: 99%
“…15 The primary objective was to determine if a secure mHealth intervention would improve contact rates between patients and providers, and positively impact the military healthcare system. Over twenty-one months, volunteers enrolled in a HIPAA-compliant mCare project using secure mobile messaging.…”
Section: Battlefield Mobile Health Applicationsmentioning
confidence: 99%
“…The mCare pilot project demonstrated the effectiveness and affordability of communicating with patients through their personal mobile devices with their care managers. 15 The initial mCare intervention consisted of a performance improvement study, which included validation and end user assessment of the technology intervention To further evaluate the impact of the mCare system, a multi-center, prospective, randomized, controlled trial of U.S. Army Soldiers conducted between April 2011 and October 2012 to measure: recovery goal awareness, contact rates; symptom inventory severity; satisfaction, general well-being, and usability. 16 All Service Members receiving care had some type of illness or injury, and therefore required long term management as they progressed through the rehabilitation process and eventually transitioned into retirement, discharge or returned to duty.…”
Section: Battlefield Mobile Health Applicationsmentioning
confidence: 99%